2010
DOI: 10.2135/cropsci2009.09.0518
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Reproductive Sink Size and Short‐term Reductions in Photosynthesis during Flowering and Pod Set

Abstract: The number of pods and seeds produced by soybean [Glycine max (L.) Merr.] is related to canopy photosynthesis during flowering. The effect of low photosynthesis during only a portion of flowering (growth stage R1 to R5), however, is not well defined. Two field experiments were conducted at Lexington, KY (38°N), with seeds sown in mid‐May in 0.76‐m rows (20 seeds m−1 of row) and all plots irrigated as needed. In 2005/2006, plants (cultivars Pennyrile and Ripley) were shaded (60% in 2005 and 80% in 2006) for 4‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 33 publications
3
24
0
1
Order By: Relevance
“…On the other hand, at higher densities, photosynthetic rates per plant were lower, as were nitrogen fixation inputs per plant. These results are consistent with studies of photosynthetic rate reduction, in which manipulations of the source, such as shading and defoliation, resulted in reductions in the number and dry weight of grains per plant (Egli, 2010;Proulx and Naeve, 2009). Additionally, with decreases in the supply of photosynthates (source) caused by the same treatments there were decreases in the rates of nitrogen fixation (Neves and Hungria, 1987).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, at higher densities, photosynthetic rates per plant were lower, as were nitrogen fixation inputs per plant. These results are consistent with studies of photosynthetic rate reduction, in which manipulations of the source, such as shading and defoliation, resulted in reductions in the number and dry weight of grains per plant (Egli, 2010;Proulx and Naeve, 2009). Additionally, with decreases in the supply of photosynthates (source) caused by the same treatments there were decreases in the rates of nitrogen fixation (Neves and Hungria, 1987).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, individual seed weight and seed number per pod were also not affected by [CO 2 ] enrichment, suggesting that the increase in seed weight with elevated [CO 2 ] was mainly caused by an increase in the number of pods and seeds produced by the greater number of nodes per plant. Seed numbers produced by soybean are also related to canopy photosynthesis during the early reproductive stage (Kokubun and Watanabe, 1981;Egli, 2010). Sameshima (2000) reported that seed number per soybean plant was positively affected by the dry matter production rate during the exponential seed growth phase.…”
Section: [Co 2 ] Effects On Seed Weight Seed [N] and Their Related mentioning
confidence: 99%
“…On the other hand, pods and seeds per unit area are associated with canopy photosynthesis or crop growth rate during flowering and pod set (growth stage R1-R5; Fehr and Caviness, 1977) (Schou et al, 1978;Jiang and Egli, 1993;Board and Tan, 1995;Egli, 2010). This association, coupled with the relatively high…”
mentioning
confidence: 99%